Pemikiran Pendidikan Islam Perspektif KH. Hasyim Asy’ari - Khoir, Mulyanto Abdullah; Aziz, Nur; Al Faizi, Ahmad Akbar (TSAQOFAH, 2025)
This research aims to explore thoughts on Islamic education from the perspective of KH. Hasyim Asy'ari, a major figure in the history of Islam in Indonesia and founder of Nahdlatul Ulama (NU). His thoughts have had a great influence on the development of Islamic education in the country, both in theoretical and practical contexts. Through a qualitative approach with literature study, this research analyzes the works of KH. Hasyim Asy'ari and the educational insights he brought forward, such as the importance of balance between intellectual and spiritual aspects in education. KH. Hasyim Asy'ari emphasizes education that is oriented towards the formation of noble morals and mastery of in-depth religious knowledge, taking into account the needs of society in a social and cultural context. The findings of this research show that his thoughts are very relevant in developing a holistic Islamic education system, which not only prioritizes academic aspects, but also moral and spiritual aspects. Therefore, KH.'s educational thinking. Hasyim Asy'ari can be used as a reference in formulating Islamic education policies that are more inclusive and in line with the needs of the times.